Coronary microvascular function and visceral adiposity in patients with normal body weight and type 2 diabetes. Issue 5 (31st March 2022) - Chowdhary, Amrit; Thirunavukarasu, Sharmaine; Jex, Nicholas; Coles, Lauren; Bowers, Charles; Sengupta, Anshuman; Swoboda, Peter; Witte, Klaus; Cubbon, Richard; Xue, Hui; Kellman, Peter; Greenwood, John; et al.
Abstract: Objective: This study sought to assess whether diabetes affects coronary microvascular function in individuals with normal body weight. Methods: Seventy‐five participants (30 patients with type 2 diabetes [T2D] who were overweight [O‐T2D], 15 patients with T2D who were lean [LnT2D], 15 healthy volunteers who were lean [LnHV], and 15 healthy volunteers who were overweight [O‐HV]) without established cardiovascular disease were recruited. Participants underwent magnetic resonance imaging for assessment of subcutaneous, epicardial, and visceral adipose tissue areas, adenosine stress myocardial blood flow (MBF), and cardiac structure and function. Results: Stress MBF was reduced only in the O‐T2D group (mean [SD], LnHV = 2.07 [0.47] mL/g/min, O‐HV = 2.08 [0.42] mL/g/min, LnT2D = 2.16 [0.36] mL/g/min, O‐T2D = 1.60 [0.28] mL/g/min; p ≤ 0.0001). Accumulation of visceral fat was evident in the LnT2D group at similar levels to the O‐HV group (LnHV = 127 [53] cm 2, O‐HV = 181 [60] cm 2, LnT2D = 182 [99] cm 2, O‐T2D = 288 [72] cm 2 ; p < 0.0001). Only the O‐T2D group showed reductions in left ventricular ejection fraction (LnHV = 63% [4%], O‐HV = 63% [4%], LnT2D = 60% [5%], O‐T2D = 58% [6%]; p = 0.0008) and global longitudinal strain (LnHV = −15.1% [3.1%], O‐HV= −15.2% [3.7%], LnT2D = −13.4% [2.7%], O‐T2D = −11.1% [2.8%]; p = 0.002) compared with both control groups. Conclusions: Patients with T2D and normal body weight do not show alterations in global stress MBF, but they do show significant increases in visceral adiposity. Patients with T2D who were overweight and had no prior cardiovascular disease showed an increase in visceral adiposity and significant reductions in stress MBF. Abstract : Changes in cardiac structure, function, perfusion and adipose tissue distribution between lean and overweight patients with T2D and HV.